Effect of Artificially Prepared Food and Algal Food on the Growth of Lebistes reticulates - Sadiq, Basharat; Butt, GhazalaYasmeen; Ahmad, Farooq; Mahmood, Rashid (Asian Journal of Chemistry, 2015)
Two algal species Chladophora aegagropila and Gomphonema geminatum was collected from botanical garden of GC University, Lahore and further processed to prepare food for guppy fish (Lebistes reticulates), bought from a local fish market of Lahore. The fish that was fed with algal species showed high trends towards growth, length and weight than fish in artificially prepared food bought from commercial market. During this research work artificially prepared food was used as control and algal food was used as experimental media. Limnological study was also conducted in which dissolve oxygen, pH, temperature, total dissolve solvents, carbonates, bicarbonates, calcium, magnesium and chloride ions were also evaluated. The high rate of growth in algal food was due to presence of more protein content than artificially prepared food.